PENGELOLAAN DAYA TARIK WISATA PURA TAMAN AYUN SEBAGAI BAGIAN DARI WARISAN BUDAYA DUNIA - Widiarta, I Nyoman (Jurnal Master Pariwisata (JUMPA); Volume 02, Nomor 02, Januari 2016DO - 10.24843/JUMPA.2016.v02.i02.p08)
This article analyses the management system of tourist attraction in Taman Ayun Temple, part of the UNESCO world heritage site listed in 2012. It discusses management strategy, community participation in enhance the attractiveness of the attraction and visitors perception. Data were obtained during a periode of research in March 2015 through interview with stakeholder and observation. The research shows that there has been a significant improvement of facilities in Taman Ayun Temple after the designation of UNESCO, such as wantilan traditional Balinese building hall, toilet, and the arrangement of space in the front of the temple which used to be for artshops or petty traders. The community participation continue through ceremonial activities, preservation of ancient relics, and preservation of cultural arts.The perception of tourists who visit Taman Ayun Temple are very good especially toward the uniqueness of the temple’s architecture, general atmosphere, condition of the road in front of the temple, and wantilan hall.
Keywords: management, tourist attraction, Taman Ayun Temple, world cultural heritage.